A beach of their own: The creation of the gender-segregated beach in Tel Aviv. Issue 1 (2nd January 2016) - Weiss, Shayna
Abstract: This article examines the struggle for gender-segregated sea bathing in Tel Aviv from the first calls for gender segregation in the 1920s until 1966, when the city of Tel Aviv established a beach for men and women to swim separately. The most effective demands for gender segregation were framed in a civic and not religious discourse. Rather than claiming that gender-segregated swimming was against Jewish values, the ultra-Orthodox party Agudat Yisrael effectively argued that a lack of separate swimming violated their rights as taxpayers who had the right to bathe in the sea just as any other Israeli citizen.